Pancreatic imaging in MEN1-comparison of conventional and somatostatin receptor positron emission tomography/computed tomography imaging in real-life setting - Kostiainen Iiro; Majala Susanna; Schildt Jukka; Parviainen Helka; Kauhanen Saila; Seppänen Hanna; Miettinen Päivi J; Matikainen Niina; Ryhänen Eeva M; Schalin-Jäntti Camilla (OXFORD UNIV PRESS, 2025)
Objective
Pancreatic neuroendocrine tumors (panNETs) are the leading cause of death in patients with multiple endocrine neoplasia type 1 (MEN1). The role of somatostatin receptor positron emission tomography/computed tomography (SSTR PET/CT) in MEN1 has not been established. The aim was to assess pancreatic imaging in MEN1 in a real-life setting.
Design
Fifty-eight patients with MEN1 [median age 40 (range 16-72) years] underwent SSTR PET/CT imaging; either as a screening tool regardless of disease stage (n = 47) or to further characterize known panNETs (n = 11). SSTR PET/CT and matched conventional imaging were blindly analyzed. We assessed the findings and the impact of SSTR PET/CT during a median follow-up of 47 months.
Results
SSTR PET/CT detected three times as many panNETs as conventional imaging (P < .001). SSTR PET/CT altered the management of 27 patients (47%). Seven patients (12%) were referred for surgery, and five (9%) received systemic treatment. In 15/25 (60%) patients with no previous panNET (n = 22) or in remission after surgery (n = 3), SSTR PET/CT identified a panNET (n = 14) or recurrence (n = 1). In eight patients, SSTR PET/CT revealed a panNET not immediately visible on conventional imaging. During a median follow-up of 47 months, three became visible on conventional imaging, but none required intervention. When SSTR PET/CT was negative, no panNETs were identified on conventional imaging during 38 months of follow-up.
Conclusions
SSTR PET/CT demonstrates high accuracy in the detection of panNETs and alters the clinical management in nearly half of the MEN1-patients. SSTR PET/CT enables timely diagnosis and staging of MEN1-related panNETs.